Enhancing livelihood and community diversity through wetland- approach to living with the wetland - Malapile, Malose (School of Architecture, Planning and Geomatics, 2025)
Numerous scholars studying urban informal settlements unanimously acknowledge the interconnected challenges these settlements face, encompassing health issues, hazardous natural surroundings, accidental human-induced fires, deficient public health infrastructure, limited social and shared spaces, and high crime rates, among other concerns. Despite multiple research and policy initiatives, there remains a limited understanding of informal settlements, often located in inadequate environments without the same services as wealthier urban areas. This enduring disparity highlights the stark contrast in living conditions between urban poor and rich communities. Masiphumelele, as one such informal settlement, encounters inadequate service delivery, exposing its residents to health and safety threats. This research project responds to these issues by delving into the quality of life in Masiphumelele. The primary goal is to explore the key factors influencing the community's well-being and to comprehend the intricate obstacles hindering spatial improvement. The research aims to investigate the spatial, social, and cultural dimensions of informal settlements, seeking to unravel the underlying causes and challenges faced by the community. Employing methods such as interviews with open-ended questions, guided walkabouts, analysis of archived newspapers, and engagement with both the community and the NGO, the research seeks a comprehensive understanding of the issues shaping the quality of life in environments that are unsafe and hazardous.The research culminates in several spatial design suggestions and proposals, offering potential solutions to enhance the quality of life in Masiphumelele